2004
DOI: 10.1111/j.1440-1797.2004.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the management of exit site infections in peritoneal dialysis patients

Abstract: Ultrasonography of the exit sites in CAPD patients is a useful adjunctive tool in the management of ESI. A sonolucent zone around the external cuff >1 mm thick following a course of antibiotic treatment and the involvement of the proximal cuff are associated with poor clinical outcome. In ESI caused by Pseudomonas aeruginosa, the clinical outcome was uniformly poor irrespective of the sonographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 9 publications
2
30
0
3
Order By: Relevance
“…TI may present as erythema, oedema, or tenderness over the subcutaneous pathway, but is often clinically occult, as shown by sonographic studies 16,35 . Ultrasonography of the exit site is a useful adjunctive tool in the management of ESI and TI 16,36 . In this study population, ultrasonography showed the presence of pericatheteral TI.…”
Section: Discussionmentioning
confidence: 75%
“…TI may present as erythema, oedema, or tenderness over the subcutaneous pathway, but is often clinically occult, as shown by sonographic studies 16,35 . Ultrasonography of the exit site is a useful adjunctive tool in the management of ESI and TI 16,36 . In this study population, ultrasonography showed the presence of pericatheteral TI.…”
Section: Discussionmentioning
confidence: 75%
“…We analyzed the influence of clinical findings on prognosis and found that exit-site infection and frequency of past peritonitis episodes were important factors. Ultrasonography can facilitate the diagnosis of exit-site infections [16]. For prevention of peritonitis from these infections, management issues, such as use of ultrasonography, antibiotic administration timing and duration, and timing of catheter replacement, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the external cuff is associated with poor clinical outcomes (287). Shaving of the external cuff, followed by re-tunnelization, as an alternative to catheter removal for treatment of a persistent ESI has been proposed if the inner cuff is not involved.…”
Section: Guideline 19 -Treatment Of Catheter-related Infectionmentioning
confidence: 99%